La dinámica vincular celos-infidelidad (2011)
ABSTRACT: The jealousy-infidelity conflict has an underlying current of interpsyche motivations as strong as fear of object loss, narcissistic need satisfaction, differentiation search, and power relationships. Feelings such as pain, hatred, sadness, fear, uncertainty, lack of trust, repentance, erratic behavior, doubts, constant dissociation, and blame are felt as much by the jealous party as by the unfaithful party. The significance of infidelity has to do with escaping the invasive object, forcing oneself to reparation, denial of the de-idealization of the love object or protecting oneself against abandonment. The frequency of this conflict in couples and its recurrence as a motive for consultation obligates psychotherapists to greater depth analysis of the complexity which underlies the dynamics of this link. The orientation theory for the presentation of this theme is basically integrated by the unconscious dynamics of object relationships, projective identification and collusion.